The Influence Of Investment On Economic Growth In Sumbagsel - I Gusti Ayu Suji Adnyani; Azansyah Azansyah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to find out how SUMBAGSEL investment affects economic growth. Panel data regression using the Eviews-12 program is the tool used in this study. Panel data covering 10 provinces in Sumatra over a period of 11 years with time series from 2012 to 2022 was used to generate the study. Overall, the results of this study indicate that investment affects economic growth positively and significantly, this study seeks to ascertain how SUMBAGSEL investment affects economic growth. Overall, the results show that. The result of F-statistic value of 251.8980 is greater than F table which is 2.578739. This means that investment affects economic growth in SUMBAGSEL .